Understanding residents' continued usage intention of community sharing platforms in smart communities in a post-COVID era: evidence from China. (26th July 2022) - He, Minghua
A community sharing platform has demonstrated its significant role in prevention and control of COVID-19 pandemic in communities throughout China. Despite its increasing popularity, the widespread adoption and continued usage intention of smart community sharing platforms by the residents is still far underexplored. Thus, this study applied the technology acceptance model (TAM) as the research framework to empirically investigate the factors influencing residents' continued intention to use community sharing platforms in the post-COVID era. Empirical results show that perceived ease of use, perceived usefulness and sharing attitude significantly impact residents' continued intention to use smart community sharing platforms and that residents' education level significantly moderates the relationships between the three kinds of antecedents and continued usage intention. This study contributes to the literature in the field of smart communities and provides practical implications for governments and platform operators to achieve sustainable development of community sharing platforms.